DESIGN AND FORMULATION OF A SHAMPOO BASED ALCOHOLIC EXTRACT OF Urtica urens L. FOR APPLICATION AGAINST HAIR LOSS. - Samaniego Joaquin, Jhonnel (2017)
I designed and formulated a shampoo containing the alcoholic extract of Urtica urens L. using an analytical, experimental and comparative method. white rabbits, New Zealand breed males (irritation test for biological evaluation of medical devices) were used. They were part of this study diagnosed with hair loss non-pathological origin; numbering 10 people were evaluated by a medical professional, for 21 days. They were subjected to microscopic observation fallen hair daily to assess whether there is increased hair diameter compared to the beginning and end of the study. fallen hair count per day throughout the treatment was obtained. Using the method of standardized hair count by 60 seconds. They were obtained as results that the percentage of hair loss reduction was 56.8% for the group of people who used the shampoo at a concentration of 2% and 32.1% for the group of people using a shampoo 5% concentration. the average diameter of fallen hair count and evaluation of fallen hairs per day were compared, using the hair counting method standardized for 60 seconds. It was able to design and make a shampoo containing alcoholic extract of Urtica urens L.; showing its effectiveness in treating hair loss achieving greater than 50% improvement and determined not produce skin irritability.